Novel Proton Conducting Solid Bio-polymer Electrolytes Based On Carboxymethyl Cellulose Doped With Oleic Acid And Plasticized With Glycerol - M. N. Chai; M. I. N. Isa (Nature, 2024)
Scientific Reports volume 6, Article number: 27328 (2016)